Morbidity and Mortality Outcome in Late Preterm Neonates at a Tertiary Care Hospital - Amin, Tahsinul; Nur, Ayesha Najma (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: The morbidity and mortality in late preterm neonates is higher than term neonates. The main reason is the relative physical and neurologic immaturity, though there is no significant difference in the weight or the size of the two groups. Objective: The study was conducted to compare the early neonatal morbidity and mortality (within first 7 days of life) in late preterm infants (34–36 6/7 weeks) with those in term neonates (37–41 6/7 weeks). Materials and Methods: This was a prospective study conducted from 01 January 2015 to 30 June 2015 in the department of Neonatology at a tertiary hospital. Results: Total 100 neonates were included in the study; fifty neonates in each group. Late preterm infants had significantly higher morbidity due to any cause, e.g. respiratory morbidity (p<0.05), jaundice (p<0.05), hypoglycemia (p<0.05), sepsis (p<0.05) and perinatal asphyxia (p<0.05). Early neonatal mortality in late preterm neonates was significantly higher than term neonates (p<0.05). Conclusion: Late preterm neonates are at high risk for morbidity and mortality as compared to term neonates. Journal of Armed Forces Medical College Bangladesh Vol.12(1) 2016: 44-47